2018
DOI: 10.1039/c8ra04286a
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of graphene quantum dots and simultaneous nanostructured self-assembly via a novel microwave-assisted method: impact on triazine removal and efficiency monitoring

Abstract: Graphene quantum dot (GQDs) assemblies from a one-step microwave reaction as bifunctional materials in remediation of triazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Absorption features of both GQDs are rather similar (Figure 3) consisting of a continuous UV absorption band associated with the sp 2 -carbon cores that became distended to the visible region derived from both surface defects and core defects linked to the double bonds of carbon and heteroatoms (nitrogen and oxygen). Both unstructured graphitic frameworks are characteristic of other carbon and graphene quantum nanodots previously reported [8,21]. As for most of carbonaceous nanodots [8], the fluorescence mechanism of GQDs is not completely understood.…”
Section: Synthesis and Characterization Of Two Types Of Graphene Quanmentioning
confidence: 97%
See 2 more Smart Citations
“…Absorption features of both GQDs are rather similar (Figure 3) consisting of a continuous UV absorption band associated with the sp 2 -carbon cores that became distended to the visible region derived from both surface defects and core defects linked to the double bonds of carbon and heteroatoms (nitrogen and oxygen). Both unstructured graphitic frameworks are characteristic of other carbon and graphene quantum nanodots previously reported [8,21]. As for most of carbonaceous nanodots [8], the fluorescence mechanism of GQDs is not completely understood.…”
Section: Synthesis and Characterization Of Two Types Of Graphene Quanmentioning
confidence: 97%
“…The nanosecond decay kinetics are dependent on the excitation wavelengths for both cases. The observation of lifetime values of a few nanoseconds suggested that the fluorescent transitions are dipole-allowed [8,21]. A possible fluorescence mechanism widely applied by most researchers is associated to an excitation-dependent emission behavior owing to multichromophoric moieties within these nanosystems, explaining that the emission is due to the presence of many different surface states while the absorption is due mainly to the core state.…”
Section: Synthesis and Characterization Of Two Types Of Graphene Quanmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond their non-toxicity, ease of synthesis, highly functionalized surface, very versatile structural properties [5][6][7][8] and significant two photon absorption properties [9], C-dots usually display an intense fluorescence due to the radiative recombination of an electron with hole after photo-excitation, usually occurring on surface trap sites [1,[10][11][12] although not always [13]. This fluorescence is very sensitive to the external environment and strongly responds to changes in environmental parameters, as for example solvent polarity [10,14], or the presence of molecules or ions in solution [12,[15][16][17], leading to the use of C-dots as sensors in solution phase. Therefore, plenty of optical investigations of the interaction between C-dots and ions or molecules in solution exist in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is well known that the surface of CDs has a key role in the emission mechanism, causing a strong interaction between the dot and, for example, solvent molecules and ions or molecules in solution [15][16][17][18]. One way to investigate these processes arising from the interaction with the external environment is the study of the fluorescence at low temperatures.…”
Section: Introductionmentioning
confidence: 99%